Euglycemic diabetes ketoacidosis associated with SGLT-2 inhibitors - review of case reports - Winciorek, Joanna; Cyran, Piotr; Jaroszyńska, Anna; Jaroszyński, Filip; Kowal, Joanna; Paleczny, Jan; Parobczak, Robert; Połujański, Paweł Jakub; Wiśniewska, Adrianna Marta (Journal of Education, Health and Sport, 2024)
AIM: Sodium-glucose cotransporter 2 (SGLT-2) inhibitors have gained significant importance in the treatment of type 2 diabetes mellitus. One of the adverse effects while using SGLT-2 inhibitors is euglycemic ketoacidosis (euDKA) - acute life-threatening emergency. METHODS: The following review of case reports was based on articles published in 2023, obtained from the PubMed databases. Key search terms included “case report”, “sglt-2”, “sglt-2i”, “sodium-glucose cotransporter inhibitors”, “dka”. “eudka”, “euglycemic ketoacidosis”. RESULTS: In the literature, cases of euDKA correlated with the use of SGLT-2 inhibitors are described. CONCLUSION: There is a need for greater observation of the frequency of the adverse effects in patients taking sodium-glucose cotransporter inhibitors (SGLT-2i) and for raising awareness among doctors about the possibility of developing euglycemic diabetic ketoacidosis during the SGLT-2 inhibitors therapy.